Recent advances in experimental and numerical methods for dynamic analysis of floating offshore wind turbines — An integrated review. (August 2022) - Subbulakshmi, A.; Verma, Mohit; Keerthana, M.; Sasmal, Saptarshi; Harikrishna, P.; Kapuria, Santosh
Abstract: Over the past decade, there has been rapid increase in the offshore wind turbine installations. The future installations will see a progression from shallow to deep waters. It necessitates the development of innovative floating platforms to support the offshore wind turbines capable of resisting coupled wind and wave forces to meet the exponential growth of energy demand. The floating offshore wind turbine (FOWT) is a complex dynamic system. There exists coupling and interaction between aerodynamics, hydrodynamics, servodynamics, structural dynamics and mooring dynamics. Various analysis methods have been developed over the time to model the complex behaviour of FOWT system and to accurately predict its response. These methods can be classified as uncoupled, partially coupled and fully coupled methods based on their degree of coupling. Each of these methods can be utilized in the specific stages of the design. This paper provides an integrated review of the recent advances in the experimental and numerical methods used for the dynamic analysis of the FOWT. Various software tools used for the numerical analysis of FOWT are also reviewed in this paper. Fully coupled experimental analysis is usually carried out using real-time hybrid simulation (RTHS) in the laboratory environment. Several possible configurations of RTHS based on different partitioning schemes are also discussed. This paper encapsulates the different methods available in the literature and will be useful for further building up the research in the analysis of FOWTs. Finally, this paper is complemented with the technical challenges and future scope identified based on the review. Highlights: Analysis and design specifications for FOWT Methods for evaluation of hydrodynamic and aerodynamic loads on FOWT Uncoupled, partially coupled, fully coupled dynamic analysis of FOWT Real Time Hybrid Simulation and control methods of FOWT Technical challenges and future scope of FOWT